The Values of Dark Heritage Post-disaster: A Study of Tsunami Cases in Banda Aceh - Zya Dyena Meutia; Arief Rosyidie; Denny Zulkaidi; Sri Maryati (International Journal of Disaster Management, 2021)
The 2004 tsunami disaster that hit Banda Aceh, one city in Indonesia as the worst affected area, has left various relics that need to be considered for their preservation. Nevertheless, it is still a debate so far because heritage preservation refers to the ordinary heritage with positive values from dark heritage after a disaster. It is important to know the significance of values in preserving relics post-disaster as commemoration and learning. In literature, there is still a lack of research about dark heritage values because of natural disasters. The purpose of this research is to explore the community's dark heritage values in encouraging post-disaster area conservation planning. Thus, the purpose of this research is to reveal and explain post-disaster area planning through the approach of dark heritage values. This research was conducted from December 2019 to April 2020 in the post-tsunami area of Banda Aceh as the most affected area with in-depth interviews with 36 informants from the local community, survivors, tourists, experts, and government to know their values. This study uses an interpretative approach because it seeks to construct the existence of dark heritage values in people's perception of seeing a post-disaster area as a heritage. The study results provide new insights that understanding a historic area is not always seen from values with a positive side. Still, dark side values also become a reference that needs to be considered to be preserved for the area's sustainability. The results showed that communities have memory, symbolic, narrative, religious, and scientific values in the post-disaster landscape.